An easy-to-fabricate clearable CuS-superstructure-based multifunctional theranostic platform for efficient imaging guided chemo-photothermal therapy. Issue 24 (8th June 2018) - Zhang, Wenlong; Xiao, Jingbo; Cao, Qing; Wang, Weiheng; Peng, Xuan; Guan, Guoqiang; Cui, Zhe; Zhang, Yongfang; Wang, Shige; Zou, Rujia; Wan, Xinjian; Qiu, Huiling; et al.
Abstract : A CuS-superstructure-based clearable drug delivery and cancer theranostic platform was constructed. Abstract : Despite drug delivery systems (DDSs) receiving ever-increasing attention, development of a simple, effective, sensitive and clearable drug delivery and multifunctional theranostic nanoplatform for cancer therapy is still highly desirable and remains a challenge. Herein, using a one-step solvothermal method, hollow acanthosphere-like CuS superstructures assembled from ∼10 nm nanoparticles (NPs) were successfully obtained and used as an efficient drug delivery and theranostic platform for photoacoustic (PA) and infrared (IR) thermal imaging-guided cancer combination therapy. The special hollow characteristic of CuS superstructures with mesoporous shells and large cavities grants them high drug loading capacity; they demonstrate near-infrared (NIR)/pH stimuli-sensitive drug release and pronounced synergetic effects of chemo-photothermal therapy both in vitro and in vivo . In particular, our as-fabricated hollow loose CuS superstructures, with easily breakable characteristic, are biodegradable and able to be cleared from the body when their therapy task is completed. This CuS-superstructure-based clearable drug delivery and "all-in-one" cancer theranostic platform might provide possibilities for improving therapeutic efficacy and minimizing adverse effects.